Rethinking COVID-19 and Beyond: Prevention, Remedies, and Recovery - Maffetone, Philip B.; Laursen, Paul B. (Frontiers in Public Health, 2022)
In a relatively short timeframe, millions of deaths and illnesses associated with COVID-19 have been reported, negatively impacting society, and incurring significant expenditure and other economic losses. This experience should serve as a wakeup call to those in public health and healthcare, along with politicians and citizens: COVID-19 is considered a predictable and preventable disaster. While various reactive responses to address the pandemic were implemented, some with adverse effects, proactive measures in the years before COVID-19 were neglected. They included allowing preventable chronic health conditions to develop, increasing the risk of infections in billions of people worldwide. In addition, another preventable global disaster, the overfat pandemic, has been growing for over 40 years, and played a key role in both rising rates of chronic disease, the comorbidities that increase the risk for COVID-19. About 80% of the world’s population is considered overfat; a condition that can directly impair immunity and increase the risk of COVID-19 severity and death, reduce effectiveness of vaccines, and reduce vitamin D levels, itself a risk for infections, including COVID-19. Excess body fat evolves primarily from poor nutrition, particularly the overconsumption of sugar and other refined carbohydrates. Sugar must be considered the new tobacco. We cannot afford another COVID-19 or similar pandemic, especially considering that it could be worse than the current one. Implementing proactive preventive lifestyle changes, rather than waiting and reacting to another disaster must begin now, starting with simple, safe, and inexpensive dietary modifications that can quickly lead to a healthier population.